2015
DOI: 10.1186/s12871-015-0016-x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of topical and intravenous JM-1232(-) on cerebral pial microvessels of rabbits

Abstract: BackgroundJM-1232(-) is a novel anesthetic agent which acts through gamma-aminobutyric acid receptors. Cerebral pial vascular effects of JM-1232(-) are unknown. We thus evaluated topical and intravenous effects of JM-1232(-) on cerebral pial microvessels in rabbits, and the extent to which carbon dioxide (CO2) reactivity is preserved.MethodsClosed cranial windows were used to visualize cerebral pial circulation in 29 Japanese white rabbits. In the first experiment, the cranial window was superfused with increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…This metabolite must be investigated further to determine the risk of unexpected prolongation of sedation and other potential adverse effects. More recently, animal studies on the cerebrovacular effects of JM-1232(-) found that intravenous administration of the compound has minimally affected vascular reactivity and further validated its safety [38,39]. However, plans for future evaluation in human studies are unclear.…”
Section: Mr04a3mentioning
confidence: 99%
“…This metabolite must be investigated further to determine the risk of unexpected prolongation of sedation and other potential adverse effects. More recently, animal studies on the cerebrovacular effects of JM-1232(-) found that intravenous administration of the compound has minimally affected vascular reactivity and further validated its safety [38,39]. However, plans for future evaluation in human studies are unclear.…”
Section: Mr04a3mentioning
confidence: 99%